Penyelesaian Sengketa Sertipikat Ganda di Pengadilan Tata Usaha Negara Denpasar - Herry Jaya Hartana; I Made Suwitra; Ida Ayu Putu Widiati (Jurnal Analogi Hukum, 2019)
The purpose of this study was to find out the legal provisions for resolving disputes over land rights related administrative Court. The certificate is a strong proof of ownership regarding physical and juridical data, contained in the measurement letter and the land book of rights. The certificate of land must be registered, as stated in Law Number 5 of 1960 concerning Basic Agrarian Principles Article 19 paragraph 1, to ensure legal certainty by the government to register land throughout the territory of the Republic of Indonesia. As is the case in Sibang Kaja Village, the existence of certificates of multiple property rights caused a dispute due to the absence of legal certainty. This case has entered and has received the decision of the State Administrative Court. Lawsuits are not accepted by administrative Court because the claim is not to the agency, but is still between individuals. Administrative Court is not authorized to try this case because it is still in the civil sphere which should be tried in the General Court. The research method used is empirical sociology, namely research that connects with the facts that exist in society in connection with the problems encountered in the study. The dispute over multiple certificates that took place in Sibang Kaja village was due to the lack of clarity on the certificate of sale & purchase and the family history, to obtain legal certainty over this dispute, the case must proceed to the General Court.